The Social as Signal in the Body of Chromatin. Issue 1 (March 2016) - Landecker, Hannah
Human social interactions and material cultures are increasingly understood as biologically consequent environmental signals. Within the explanatory framework of epigenetics, such signals become biologically inscribed when transduced into bodies as persistent patterns of molecular conformation. In the life sciences, persistence of the social as the biological is understood as establishment of gene expression potentials, physiological changes, or epigenetic memories. How did the social become interchangeable with the environmental? When did both become scientifically graspable as signals? This article recounts the history of how hormone biologists came to think in terms of signal transduction in the late 1960s. This cybernetic legacy is important for understanding the 'environmental turn' of epigenetics. To understand the social as signal in the present moment – a post-cybernetic rather than post-genomic moment – the theory of the signal must itself be excavated and analysed.